Nucleotide sequence and distribution of the pTR2030 resistance determinant (hsp) which aborts bacteriophage infection in lactococci. - Hill, C (1990)
The lactococcal plasmid pTR2030 encodes resistance to bacteriophage attack via two mechanisms, an abortive-infection mechanism, designated Hsp, and a restriction and modification system. We present the complete sequence of the hsp structural gene. The gene is 1,887 base pairs in length and encodes a protein with a predicted molecular mass of 73.8 kilodaltons. The upstream region was cloned in a promoter-screening vector and shown to direct the constitutive expression of the cat-86 gene. An internal probe was used to determine the distribution of the hsp sequence in industrially significant lactococcal strains and to evaluate its relatedness to another lactococcal plasmid implicated in an abortive-infection-type mechanism, pNP40. No homology was detected, suggesting that this gene is not widely distributed in lactococci. Therefore, there are at least two independent abortive-infection genotypes in lactococci.